Ethical challenges related to capacity, competence and autonomy in individuals with dementia - Delineau, Valeska; Duarte, Ivone; Ferreira, Ana Rita; Fernandes, Lia (Acta Bioethica, 2025)
Dementia is a syndrome characterised by the development of multiple cognitive deficits and behavioural changes that significantly interfere with various aspects of life. The study aims to discuss capacity, competence and autonomy in individuals with dementia, and some ethical challenges related to these concepts, such as healthcare decision-making capacity, financial capacity, driving and voting. Secondarily, we aim to discuss a new ethical issue emerging from using artificial intelligence and machine learning to improve autonomy in individuals with dementia. Furthermore, we will discuss the ethical importance of obtaining informed consent for healthcare decision-making and Advance Care Planning in dementia patients. This study provides a comprehensive overview of the complex issues related to autonomy and competence in individuals with dementia, highlighting the importance of striking a balance between upholding individual rights and protecting the well-being of those affected by the disease. In conclusion, the study emphasizes the importance of Advance Care Planning in helping patients, families, caregivers, and healthcare professionals address ethical issues related to autonomy, capacity, and competence in dementia care.